Political Economy Aspects of Fuel Subsidies : A Conceptual Framework - Strand, Jon (World Bank, Washington, DC, 2013)
While notoriously inefficient, fuel subsidies are widespread, and in many cases politically stable. This paper discusses and models various political economy aspects of fuel subsidies, focusing on gasoline and kerosene. Both economic and political are considered to explain differences in subsidies, with particular focus on democratic and autocratic governments. A political process is modeled whereby a promise of low fuel prices is used in democracies to attract voters, and in autocracies to mobilize support among key groups. Subsidies to fuels are viewed as either easier to observe, easier to commit to, easier to deliver, or better targeted at core groups, than other public goods or favors offered by rulers. Easier commitment and delivery than for regular public goods can explain the high prevalence of such policies in autocracies, and also in young democracies where the capacity to commit to or deliver complex public goods is not yet fully developed. The analysis provides a framework for empirical testing and verification.